Acranthera sinensis C. Y. Wu (Rubiaceae): a new distributional record from Vietnam - Quang, Bui Hong; Khang, Nguyen Sinh; Chinh, Vu Tien; Hieu, Nguyen Quang (Academia Journal of Biology, 2016)
Acranthera sinensis C.Y. Wu (Rubiaceae), previously known only from China, is newly recorded from Vietnam. A morphological description and color illustrations, morphological comparison of Acranthera sinensis with Acranthera siamensis, together with short notes, map on the distribution, ecology, habitat and conservation of the species are provided.